Kebijakan Hukum Pidana terhadap Penyalahgunaan Narkotika Jenis Baru - Fernando Seran; Jimmy Pello; Rudepel Petrus Leo (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Narcotics are substances that cause certain effects for those who use them and put them into their bodies. Along with the development of the times, the types of drugs are increasing and have various variations. One example of a new type of drug is gorilla tobacco. Criminal Law Policy Against New Types of Narcotics Abuse. This study uses a normative juridical research type with a Philosophical approach, Criminal Law Political Approach, legislation, case approach and examines the contents of various legal sources, both books, journals and other related legal sources to answer the aspects that are the focus of the research. The results of this study indicate that in 2022 31,420 incidents were caused by an increase in the abuse of new types of narcotics (New Psychoactive Substances) which in previous years were not registered in the appendix to Law Number 35 of 2009, this caused a Legal Vacuum regarding the New Type of Narcotics. In addition, the author also analyzes the law enforcement against new types of narcotics (gorilla tobacco) in a review of Law Number 35 of 2009 concerning Narcotics and the form of criminal responsibility carried out by perpetrators of gorilla tobacco abuse in the decision of the District Court Number 32/Pid.sus/2021/PN Rtg.